Effective interactions in Ricci-Based Gravity below the non-metricity scale - Adrià Delhom; Victor Miralles; Ana Peñuelas (European Physical Journal C: Particles and Fields, 2020)
Abstract We show how minimally-coupled matter fields of arbitrary spin, when coupled to Ricci-based gravity theories, develop non-trivial effective interactions that can be treated perturbatively only below a characteristic high-energy scale $$Λ _{Q}$$ ΛQ . We then use this interactions to set bounds on the high-energy scale $$Λ _{Q}$$ ΛQ that controls departures of Ricci-Based Gravity theories from General Relativity. Particularly, for Eddington-inspired Born-Infeld gravity we obtain the strong bound $$ |κ |<10^{-26} \text {m}^5 \text {kg}^{-1}\text {s}^{-2} $$ |κ|<10-26m5kg-1s-2 .